The ATLAS3D project - IX. The merger origin of a fast- and a slow-rotating early-type galaxy revealed with deep optical imaging: first results - Duc, P; Cuillandre, J; Serra, P; Michel-Dansac, L; Ferriere, E; Alatalo, K; Blitz, L; Bois, M; Bournaud, F; Bureau, M; Cappellari, M; Davies, R; et al. (2011)
The mass assembly of galaxies leaves imprints in their outskirts, such as shells and tidal tails. The frequency and properties of such fine structures depend on the main acting mechanisms - secular evolution, minor or major mergers - and on the age of the last substantial accretion event. We use this to constrain the mass assembly history of two apparently relaxed nearby early-type galaxies (ETGs) selected from the ATLAS3D sample, NGC 680 and 5557. Our ultra-deep optical images obtained with MegaCam on the Canada-France-Hawaii Telescope reach 29 magarcsec-2 in thegband. They reveal very low surface brightness (LSB) filamentary structures around these ellipticals. Among them, a gigantic 160kpc long, narrow, tail east of NGC 5557 hosts three gas-rich star-forming objects, previously detected in Hi with the Westerbork Synthesis Radio Telescope and in UV withGALEX. NGC 680 exhibits two major diffuse plumes apparently connected to extended Hi tails, as well as a series of arcs and shells. Comparing the outer stellar and gaseous morphology of the two ellipticals with that predicted from models of colliding galaxies, we argue that the LSB features are tidal debris and that each of these two ETGs was assembled during a relatively recent, major wet merger, which most likely occurred after the redshiftz≃ 0.5 epoch. Had these mergers been older, the tidal features should have already fallen back or be destroyed by more recent accretion events. However, the absence of molecular gas and of a prominent young stellar population in the core region of the galaxies indicates that the merger is at least 1-2 Gyr old: the memory of any merger-triggered nuclear starburst has indeed been lost. The star-forming objects found towards the collisional debris of NGC 5557 are then likely tidal dwarf galaxies. Such recycled galaxies here appear to be long-lived and continue to form stars while any star formation activity has stopped in their parent galaxy. The inner kinematics of NGC 680 is typical for fast rotators which make the bulk of nearby ETGs in the ATLAS3D sample. On the other hand, NGC 5557 belongs to the poorly populated class of massive, round, slow rotators that are predicted by semi-analytic models and cosmological simulations to be the end-product of a complex mass accretion history, involving ancient major mergers and more recent minor mergers. Our observations suggest that under specific circumstances a single binary merger may dominate the formation history of such objects and thus that at least some massive ETGs may form at relatively low redshift. Whether the two galaxies studied here are representative of their own sub-class of ETGs is still an open question that will be addressed by an on-going deep optical survey of ATLAS3D galaxies. © 2011 The Authors Monthly Notices of the Royal Astronomical Society © 2011 RAS.